1977
DOI: 10.1017/s0022112077002080
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory models of sea straits

Abstract: Two basins maintained at different densities are connected by a relatively shallow strait. If the strait is short, the flow is such that the Froude number is unity. The thickness of the intermediate layer, between the outflow and the inflow, is controlled by the requirement that the Richardson number be critical; this thickness is always about one-fifth of the total depth, both in these experiments and in the Strait of Gibraltar. If the strait is long, the Froude number is less than unity in the interior but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 3 publications
1
29
0
Order By: Relevance
“…Turner [1973] used observations by Browning [1971] to argue for a limiting structure controlled by a Richardson number criterion. Anati et al [1977] gave evidence that the thickness of the interface between the inflow and the outflow in a strait is controlled by a Richardson number criterion, combined with a Froude number criterion. Turner [1973] already illustrated how a Richardson number criterion can allow a 'sheet' and 'layer' structure as observed by Woods [1969].…”
Section: = 025 (2)mentioning
confidence: 99%
“…Turner [1973] used observations by Browning [1971] to argue for a limiting structure controlled by a Richardson number criterion. Anati et al [1977] gave evidence that the thickness of the interface between the inflow and the outflow in a strait is controlled by a Richardson number criterion, combined with a Froude number criterion. Turner [1973] already illustrated how a Richardson number criterion can allow a 'sheet' and 'layer' structure as observed by Woods [1969].…”
Section: = 025 (2)mentioning
confidence: 99%
“…Then from (89), n ~ ~, R ~ O. Expeciments by Stornmel and Farmer (1953) and Anati, Assaf and Thompson (1977) confirm the prediction that the two fluids have equal thicknesses in thoroughly mixed estuaries with small fresh water influx and I have derived this result theoretically (Long, 1976a). A second special case is one in which n = 0 so that no salt water enters and fresh water fills the estuary.…”
Section: Strongly Mixed Estuariesmentioning
confidence: 52%
“…Experiments by Stornmel and Farmer (1953), Assaf and Hecht (1974) and Anati, Assaf, and Thompson (1977) have shown that critical conditions do tend to occur in a variety of straits in laboratory models. If the strait is long, friction becomes important and critical conditi6ns occur at the ends of the strait.…”
Section: Strongly Mixed Estuariesmentioning
confidence: 98%
“…Their results indicated that the interface is almost flat inside a strait, but the interface curves sharply at a control section (the strait's opening). This result is supported by a laboratory study [Anati et al, 1977]. However, the model is a kinematic theory which does not explain the nature of flow transition at a control section.…”
Section: Introductionmentioning
confidence: 65%